Aplikasi Simulasi Berkendara dengan Metode Fuzzy Logic Menggunakan Phonegap - Pahala Situmeang; NM Faizah; Panser Karo Karo (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2023)
Android-Based Car Driving Simulation Application is an application used to obtain information about driving and caring for a car using smartphone support media. This is based on the increase in car accidents from year to year. The lack of information and the lack of knowledge of car drivers about driving information has made the author make a Car Driving Simulation application for the needs of visitors in using and accessing this application. Remembering technology is like a gadget that is no longer difficult to obtain, in fact it is possible for all people to have it. The application is designed with a smartphone that uses the Android operating system. Applications are made based on information needs for motorists. This application has gone through the stages of testing on four Android smartphone devices. This application is made using Phonegap with HTML and CSS programming languages and runs on the Kitkat version of the Android operating system as a minimum requirement.